Curative pelvic exenteration for recurrent cervical carcinoma in the era of concurrent chemotherapy and radiation therapy. A systematic review. Issue 8 (August 2015) - Sardain, H.; Lavoue, V.; Redpath, M.; Bertheuil, N.; Foucher, F.; Levêque, J.
Abstract Objective Pelvic exenteration requires complete resection of the tumor with negative margins to be considered a curative surgery. The purpose of this review is to assess the optimal preoperative evaluation and surgical approach in patients with recurrent cervical cancer to increase the chances of achieving a curative surgery with decreased morbidity and mortality in the era of concurrent chemoradiotherapy. Methods Review of English publications pertaining to cervical cancer within the last 25 years were included using PubMed and Cochrane Library searches. Results Modern imaging (MRI and PET-CT) does not accurately identify local extension of microscopic disease and is inadequate for preoperative planning of extent of resection. Today, only half of pelvic exenteration procedures obtain uninvolved surgical margins. Conclusion Clear margins are required for curative pelvic exenterations, but are poorly predictable by pre-operative assessment. More extensive surgery, i.e. the infra-elevator exenteration with vulvectomy, is a logical surgical choice to increase the rate of clear margins and to improve patient survival following surgery for recurrent cervical carcinoma.